2015
DOI: 10.1266/ggs.90.79
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of genome-wide gene expression patterns in the seedlings of nascent allohexaploid wheats produced by two combinations of hybrids

Abstract: Allopolyploidization in plants is an important event that enhances heterosis and environmental adaptation. Common wheat, Triticum aestivum (AABBDD), which is an allohexaploid that evolved from an allopolyploidization event between T. turgidum (AABB) and Aegilops tauschii (DD), shows more growth vigor and wider adaptation than tetraploid wheats. To better understand the molecular basis for the heterosis of hexaploid wheat, we systematically analyzed the genomewide gene expression patterns of two combinations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Current literature suggests that hybridization, rather than the increase in ploidy level, has a greater impact on post‐allopolyploidization gene expression patterns (Albertin et al, 2006; Chelaifa et al, 2010; Hegarty et al, 2005, 2006; Jung et al, 2015; Li et al, 2018; Wang et al, 2006). Our results are consistent with this view, as there are no clear differences in gene expression patterns between the allopolyploid and homoploid hybrid systems (Figures 2–5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Current literature suggests that hybridization, rather than the increase in ploidy level, has a greater impact on post‐allopolyploidization gene expression patterns (Albertin et al, 2006; Chelaifa et al, 2010; Hegarty et al, 2005, 2006; Jung et al, 2015; Li et al, 2018; Wang et al, 2006). Our results are consistent with this view, as there are no clear differences in gene expression patterns between the allopolyploid and homoploid hybrid systems (Figures 2–5).…”
Section: Resultsmentioning
confidence: 99%
“…Also consistent is our result suggesting that hybridization, rather than change in ploidy level, is the major driver of hybrid expression patterns, as this mechanism is dependent on genome merger, but independent of an increase in ploidy. Data from studies on other allopolyploid and homoploid hybrid species including Senecio (Hegarty et al, 2005, 2006), Brassica (Albertin et al, 2006), Arabidopsis (Wang et al, 2006), Spartina (Chelaifa et al, 2010), wheat (Jung et al, 2015) and Cyprinidae fish (Li et al, 2018) have also suggested that genome merger has a greater effect on gene expression patterns than an increase in ploidy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The suite of potential biological responses, both rapid and longer term, employed by the allopolyploid in response to genome shock have many potential manifestations, including genomic restructuring (Lim et al 2008;Wu et al 2015;Qin et al 2016;Wang et al 2018) and gene loss (Scannell et al 2006;Gordon et al 2009;Vallejo-Marín et al 2015). Although the impact of allopolyploidy is most often viewed through the lens of nuclear genomic studies, organellar genomes (Sloan et al 2018), small RNAs (Ha et al 2009;Jiao et al 2018) and the gene expression profiles of allopolyploid species (Yoo et al 2014;Jung et al 2015) are also affected. Extensive changes in allopolyploid gene expression ('transcriptome shock') are driven by the mixing of two dissimilar and poorly co-adapted sets of transcription factors and chromatin signatures (Cox et al 2014).…”
Section: Introductionmentioning
confidence: 99%